Spectrum of Inherited Bleeding Disorder with Special Reference to von Willebrand Disease in Eastern India - Ahmad, Nehal; Das, Subhajit; Shukla, Jyoti; Hassan, Mohammad Jaseem (Journal of Laboratory Physicians, 2022)
Background The objective of this study is to study the prevalence, clinical spectrum, and hematological profile of inherited bleeding disorder with special reference to von Willebrand disease in eastern India.Materials and Methods This prospective study was done in a tertiary care center in the eastern part of India over 2 years. Detailed history and clinical findings were noted in a proforma. Laboratory analysis included prothrombin time, activated partial thromboplastin time, bleeding time, and fibrinogen assay along with tests related to specific factor assay.Results One hundred and five patients were diagnosed as suffering with the inherited bleeding disorder out of a total of 1,204 patients. The age of patients ranged from 13 days to 35 years. The most common presenting clinical feature was prolonged bleeding after cut (76.19%). Out of 105 patients, 97 patients (92.38%) had coagulation defect, 5 patients (4.76%) had von Willebrand disease (vWD), and 3 patients (2.85%) had platelet defect. Most common coagulation defect was hemophilia A (84 cases), followed by hemophilia B (8 cases). Other rare congenital factor deficiencies were seen in five cases (5.15%). Only platelet defect was Glanzmann's thrombasthenia (GT). The age of vWD patients ranged from 4.5 years to 24 years. Forty percent patients with vWD disease were type 1 followed by 40% of type 2N and 20% of type 3 vWD.Conclusion vWD was not so common in eastern India. vWD was present only in 4.76% cases in this study. The most common coagulation defect was hemophilia A (86.59%) in our study. GT was present in only 2.85% cases.
Keywords: bleeding; Glanzmann's thrombasthenia; hemophilia; von Willebrand disease